Memetakan Ruang Digital sebagai Area Praktik Pekerjaan Sosial - Flores G. Mayaut (Yayasan Literasi Sains Indonesia, 2026)
The development of digital technology has fundamentally changed the structure and dynamics of social life, creating digital space as a new arena for social interaction, meaning-making, and the distribution of social risk. This article aims to map digital space as an area of ​​social work practice by examining its characteristics, opportunities, and emerging challenges. Using a qualitative-descriptive approach through critical literature review and conceptual analysis, this study highlights that digital space functions not only as a means of communication but also as a social ecosystem that shapes relations of power, identity, and participation, and gives rise to new forms of vulnerability, such as online violence, unequal digital access, disinformation, and the exploitation of personal data. The study's findings indicate that social work practice in the digital era requires a redefinition of the role of social workers, from mere providers of conventional services to agents capable of conducting technology-based interventions with preventive, promotive, and advocative approaches. Digital space provides opportunities to expand service reach, strengthen community participation, and develop intervention models that are more adaptive and responsive to the needs of vulnerable groups. This study confirms that mapping digital space as an area of ​​social work practice is a strategic step to maintain the relevance and sustainability of the profession amidst social changes caused by digitalization. His contribution to the formulation of a conceptual framework that can be used as a basis for developing contextual social work policies, education, and practices that are oriented towards social justice in the digital era.